Individual Absorptive Capacity Of Host-Country National (Hcn) Workers Of Foreign Mnc(S) In Electrical And Electronic Sector In Malaysia - Ahmad, Fakhrorazi (2014)
The main purpose of this study is to provide an empirical examination of individual absorptive capacity, its antecedent and outcomes, as well as improve the individual absorptive capacity and individual knowledge acquisition constructs. On that basis, the new validated individual absorptive capacity construct that has reflectively measured in three dimensions, namely the ability to identify, assimilate, and apply knowledge was successfully established. For the new validated individual knowledge acquisition construct, it has been identified to form a single composite measure. Underpinned with social cognitive theory (SCT), the researcher has designed the theoretical framework by which some hypotheses were later developed and tested. In the data collection process, the study used a sample taken from the MIDA directory, which includes foreign MNC companies engaged in the electrical and electronics sector in Malaysia. The unit of analysis is the individual at a supervisory (executive) level rank or higher. For data collection purposes, a total of 1245 questionnaires were distributed via mail survey and the drop-and-collect approach. The response rate was 28 percent (345 cases) with an 88.4 percent usability rate (305 cases). The data was then screened and validated before it was tested using Variance-based SEM. The test results, in addition to answering the research hypotheses, showed that the variables in the model fit nicely with each other. In the hypotheses test, the study provided evidence that individual absorptive capacity was anteceded by organizational culture (OC), and positively influenced individual innovative behavior (IIB) and individual knowledge acquisition (IKA). In addition to these anticipated findings, the study also revealed the unexpected discovery on the moderating hypotheses. Further possible explanations related to the hypotheses results were then explored in the discussion chapter.